Highly Porous Sr/Mg‐Doped Hardystonite Bioceramics from Preceramic Polymers and Reactive Fillers: Direct Foaming and Direct Ink Writing. Issue 6 (31st October 2018) - Elsayed, Hamada; Gardin, Chiara; Ferroni, Letizia; Zavan, Barbara; Colombo, Paolo; Bernardo, Enrico
Abstract : Novel hardystonite‐based bioceramics are obtained by thermal treatment, in air, of silicone resins and reactive fillers. Using commercial silicones embedding SrO and MgO precursors, in addition to CaO and ZnO precursors, a quite complex solid solution (Ca1.4 Sr0.6 Zn0.85 Mg0.15 Si2 O7 ) can be achieved, at 1100 °C, instead of pure hardystonite (Ca2 ZnSi2 O7 ), with improvements in biocompatibility and bioactivity. Highly porous foams are obtained by gas evolution at the early stage of heat treatment (at 300–350 °C), from the dehydration of active filler present in hydrated form (Mg(OH)2 ). Additionally, direct ink writing of silicone‐based pastes is used for the manufacturing of scaffolds with non‐stochastic pore architecture. In the latter case, strong scaffolds (with compressive strength exceeding ≈12 MPa) are obtained by adding fine glass powders as an additional filler. This addition enhances the viscous flow upon firing, but do not compromise the phase evolution, owing to the exact match in the composition between glass and silicone/filler mixture. Abstract : Sr/Mg‐doped hardystonite bioceramics is obtained simply by heat treatment, in air, of commercial silicone resins mixed with reactive fillers. The use of silicone‐based pastes enables direct foaming, by gas release (in turn caused by dehydration of selected fillers), as well as direct ink writing.